Modest policy interventions - Eric M. Leeper; Tao Zha (Federal Reserve Bank of Atlanta, 2003)
The authors present a theoretical and empirical framework for computing and evaluating linear projections conditional on hypothetical paths of monetary policy. A modest policy intervention does not significantly shift agents' beliefs about policy regime and does not induce the changes in behavior that Lucas (1976) emphasizes. Applied to an econometric model of U.S. monetary policy, the authors find that a rich class of interventions routinely considered by the Federal Reserve is modest and their impacts can be reliably forecast by an identified linear model. Modest interventions can shift projected paths and probability distributions of macro variables in economically meaningful ways.
Keywords: 330; Equilibrium (Economics); Monetary policy; Macroeconomics; Inflation (Finance); Econometric models